The Citizen’s Charter as a Governance Innovation for Transparent and Accountable Village Services - Sari, Risma; Irwan, Irwan; Barisan, Barisan; Lumintao, Jornie (Jurnal Studi Ilmu Pemerintahan, 2025)
Transparency and accountability are fundamental elements in achieving good governance and citizen-oriented public services. This study aims to evaluate the implementation of the Citizen’s Charter in enhancing transparency, accountability, and the quality of public services at the Lasiwala Village Office, Sidenreng Rappang Regency, Indonesia. The Citizen’s Charter represents an innovative governance tool designed to promote open information, clarify service standards, and strengthen community participation. Adopting a qualitative approach through in-depth interviews, observation, and document analysis, this study analyzed data using NVivo 12 Plus software. The findings indicate that the principles of the Citizen’s Charter, particularly transparency and efficiency, have begun to be integrated into village service delivery. However, several challenges remain, including limited human resources, insufficient socialization to citizens, and incomplete documentation of standard operating procedures (SOPs). The study highlights the need for capacity-building programs and the institutionalization of participatory mechanisms to sustain accountability in local governance. This research contributes to theoretical understanding of community-based accountability and offers a practical model for improving transparency and responsiveness in village-level public service systems.